Climate change and the allocation of time - Marie Connolly (IZA World of Labor, 2018)
Understanding the impacts of climate change on time allocation is a major challenge. The best approach comes from looking at how people react to short-term variations in weather. Research suggests rising temperatures will reduce time spent working and enjoying outdoor leisure, while increasing indoor leisure. The burden will fall disproportionately on workers in industries more exposed to heat and those who live in warmer regions, with the potential to increase existing patterns of inequalities. This is likely to trigger an adaptation, the scope and mechanisms of which are hard to predict, and will undoubtedly entail costs.
Keywords: Q54; J22; 330; climate change; weather; time use; well-being; adaptation